1985
DOI: 10.2136/sssaj1985.03615995004900010053x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Basalt in Soils of Western Oregon

Abstract: Basalt alteration from different pedo‐microenvironments in western Oregon was studied using petrographic, electron microscope, X‐ray diffraction, and differential thermal techniques. Initial alteration was similar in each environment and consisted primarily of mineral dissolution associated with the formation of etch pits and hairline cracks and the development of isotropic domains within feldspar phenocrysts. The stage of alteration characterized by secondary mineral formation was distinctly microenvironment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 0 publications
2
24
0
2
Order By: Relevance
“…Locally, smectite may occur (Nelson et al, 2013;Dessert et al, 2003;Chadwick et al, 2003;Johnsson et al, 1993), and may be an intermediate phase of weathering before recrystallization to kaolinite or halloysite (Glassman and Simonson, 1985;Eggleton et al, 1987). Joussein (2016) and Vitousek et al (2007) suggested that soil mineralogy ripens through a series of steps from allophane or imogolite to halloysite and finally kaolinite on a time frame of ~1 m.y.…”
Section: Mineralogy Of Hawaiian Lateritesmentioning
confidence: 99%
“…Locally, smectite may occur (Nelson et al, 2013;Dessert et al, 2003;Chadwick et al, 2003;Johnsson et al, 1993), and may be an intermediate phase of weathering before recrystallization to kaolinite or halloysite (Glassman and Simonson, 1985;Eggleton et al, 1987). Joussein (2016) and Vitousek et al (2007) suggested that soil mineralogy ripens through a series of steps from allophane or imogolite to halloysite and finally kaolinite on a time frame of ~1 m.y.…”
Section: Mineralogy Of Hawaiian Lateritesmentioning
confidence: 99%
“…Excess salt was removed by washing the samples with water and absolute methanol, and slides for XRD analysis were prepared by a smear method (Theisen and Harward, 1962). Slides were analyzed in a constant humidity environment (54% relative humidity) on a Norelco diffractometer (CuKa, 43 kV, 28 mA) using the characterization treatments outlined by Glasmann and Simonson (1985).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in permeability and leaching conditions associated with the microfracture network determine different environments in the crystals. Even in crystals of small size, <0.1 mm, solutions circulate along preferential pathways and the duration of contact varies accordingly, thus resulting in a different evolution for each portion of the crystal (Glasmann and Simonson, 1985).…”
Section: Nature and Origin Of The Secondary Mineralsmentioning
confidence: 99%